Contemporary Bank Interest Law in Fath Adz Dzara'i's Review - Abd Basir; Achmad Musyahid; Rina Rosia; Muhammad Hamsah (al-Afkar, Journal For Islamic Studies, 2023)
The spirit of anti-usury in various Muslim communities in the country is getting more intense and active. one of which is that it can be seen from the increasing number of customers at Islamic banks with a significant number of developments from time to time. However, the reality that occurs in conventional banking is still the choice of customers as Muslims, including to borrow money or funds. Of course, conventional banking applies an interest system (Conventional Banking Applies), both loan interest and deposit interest. In Indonesia, the fatwa regarding the halal interest of banks  is not very popular. Most Islamic scholars and organizations in Indonesia have issued a fatwa that bank interest is usury which is forbidden. The concept in the past was that transactions occurred individually, where someone borrowed money and the person who gave the loan charged interest. While transactions that include borrowing money from banks are more complex or more complete. In the matter of usury in bank interest, various opinions of scholars, there are scholars who argue that bank interest is lawful on the grounds that the practice of usury in the past was not the same as the phenomenon of bank interest that occurred at the moment now. The main problem is: is bank interest included in the usury category or not included in the usury category, Bank interest law in the perspective of contemporary Islamic law is permissible if there is a need or benefit by adhering to the principle "Mȃ hurrima lisadd al-dzarî'at ubîha li alhȃjat aw al-mashlahat.